2009
DOI: 10.1001/jama.2009.1409
|View full text |Cite
|
Sign up to set email alerts
|

Using Effectiveness and Cost-effectiveness to Make Drug Coverage Decisions

Abstract: Context National public insurance for drugs is often based on evidence of comparative effectiveness and cost-effectiveness. This study describes how that evidence has been used across 3 jurisdictions (Australia, Canada, and Britain) that have been at the forefront of evidence-based coverage internationally.Objectives To describe how clinical and cost-effectiveness evidence is used in coverage decisions both within and across jurisdictions and to identify common issues in the process of evidence-based coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
228
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(239 citation statements)
references
References 26 publications
5
228
0
6
Order By: Relevance
“…Nine studies [10][11][12][13][14][15][16][17][18] compared HTA coverage recommendations for medicines in more than one country and identified important variations, where agreement ranged from poor to moderate [10,11,13]. The countries compared included Canada, Australia, England, Scotland, France, New Zealand, and other European countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies [10][11][12][13][14][15][16][17][18] compared HTA coverage recommendations for medicines in more than one country and identified important variations, where agreement ranged from poor to moderate [10,11,13]. The countries compared included Canada, Australia, England, Scotland, France, New Zealand, and other European countries.…”
Section: Introductionmentioning
confidence: 99%
“…The countries compared included Canada, Australia, England, Scotland, France, New Zealand, and other European countries. One study concluded that the most common reasons for differing recommendations related to the HTA process and context [10]. Another study highlighted cross-country variations for seventeen of the most expensive medicines, but the extent of, and reasons for these differences were not explored [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence from surrogate end points may not only expedite the regulatory approval of new health technologies but also inform coverage and reimbursement decisions. Over the past decade, between 27% and 50% of submissions to the National Institute for Health and Care Excellence (NICE) in the United Kingdom, the Pharmaceutical Benefits and Advisory Committee in Australia and the Common Drug Review in Canada were based on surrogate end points 3 .…”
Section: I N K To O R I G I N a L A Rt I C L Ementioning
confidence: 99%
“…Experience from countries such as Australia, Canada, Thailand and the UK indicates that health technology assessment (HTA), a ''multidisciplinary policy research, in generating evidence to inform prioritization, selection, introduction, distribution, and management of interventions for health promotion, disease prevention, diagnosis and treatment, and rehabilitation and palliation'', can be helpful in supporting this purpose [4][5][6][7]. In Thailand and the UK, in particular, decision makers not only successfully include interventions in their benefits packages but are also able to decline including unnecessarily costly or unproven interventions as well as set standards for other countries in the regions.…”
mentioning
confidence: 99%